Rationalising Social Forestry Objectives - Chowdhary, R. L. (Indian Forester, 1978)
The dichotomy of production forestry and social forestry was clearly brought out by Westoby (1968), who defined social forestry as forestry "which aims at producing flow of protection and recreation benefits for the community". The National Commission on Agriculture (1972, 1973) agreed with this concept of social forestry, but felt that social forestry, should also include, interalia, raising of plantations for the supply of small timber, fuel, forage, shelterbelts around agriculture fields etc. Westoby (1968) probably neve meant these objectives of providing, timber, fuel and fodder, in his concept of social forestry, which he visualised as providing such type of goods and services, which would be akin to "public goods" and "mixed goods" in Economics parlance. Merely because some projects cannot stand the rigid tests of social benefit/cost analysis, there is no justification for inclusion of such relatively unproductive schemes in social forestry and much less, to seek to finance it through public funds. The goods and services like production of small timber, fuel, fodder supply, protection of agricultural fields against wind, belong to the realm of production forestry and Westoby’s principle that "production forestry should pay" must be made applicable to such schemes. The goals for social forestry, as laid out by Westoby (1968), "should be determined by the amount of investment the community is pepared to allocate to secure the desired social benefits" .